Fungal community succession contributes to product maturity during the co-composting of chicken manure and crop residues. (May 2021) - Xie, Guixian; Kong, Xiaoliang; Kang, Jialu; Su, Ning; Fei, Jiangchi; Luo, Gongwen
Graphical abstract: Highlights: Varying fungal community was related with change in composting micro-environment. Material composition and composting phase influenced fungal community succession. Composting reduced pathogenic and symbiotrophic fungi but increased saprotrophic guild. Functional taxa succession of fungal community was expected to predict compost maturity. Abstract: The succession of the fungal community during the co-composting of chicken manure and crop residues and its role in relation to compost maturity was deciphered using Illumina sequencing and FUNGuild (Fungi + Functional + Guild) tool. In the maturation phase of composting, the relative abundance of pathogenic and symbiotrophic fungi decreased by 68%-85% and 145%-622%, respectively, as compared to the initial phase, which showed 574%-720% increase in the saprotrophic guild. The pathogenic and saprotrophic fungi abundance was correlated to compost maturity represented by germination index and humic spectroscopic ratio ( p  < 0.05). Random forest analysis and structural equation modeling elucidated the positive effects of the aforementioned fungal taxa on compost maturity, and these effects were mediated by the micro-environmental variables, such as temperature, NH4 + -N/NO3 − -N ratio and total organic carbon content. Our study outlines the importance of fungal community succession for improving composting performance and efficiency.